2002
DOI: 10.1203/00006450-200204000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Active Compression-Decompression Cardiopulmonary Resuscitation with the Inspiratory Threshold Valve in a Young Porcine Model of Cardiac Arrest

Abstract: Active compression-decompression (ACD) cardiopulmonary resuscitation (CPR) with the inspiratory threshold valve (ITV) has been recently recommended by the American Heart Association for treatment of adults in cardiac arrest (class IIb: alternative, useful intervention), but this new technique has never been used in a pediatric population. Thus, this study was designed to evaluate ACD ϩ ITV CPR in a young porcine model of cardiac arrest. After 10 min of ventricular fibrillation, and 8 min of standard CPR, ACD ϩ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 18 publications
2
18
0
1
Order By: Relevance
“…Consistent with earlier animal and human studies, [1][2][3][4][5]11,12 the results from this first clinical comparison of S-CPR versus ACDϩITD CPR demonstrated that there was a significant improvement in ROSC and 1-and 24-hour survival rates for all patients in the new treatment group. The improvement in short-term survival was notable in patients with a witnessed arrest; however, the short-term impact on survival with ACDϩITD CPR was most striking in patients with VF who were not resuscitated by 3 sequential DC shocks before randomization.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with earlier animal and human studies, [1][2][3][4][5]11,12 the results from this first clinical comparison of S-CPR versus ACDϩITD CPR demonstrated that there was a significant improvement in ROSC and 1-and 24-hour survival rates for all patients in the new treatment group. The improvement in short-term survival was notable in patients with a witnessed arrest; however, the short-term impact on survival with ACDϩITD CPR was most striking in patients with VF who were not resuscitated by 3 sequential DC shocks before randomization.…”
Section: Discussionsupporting
confidence: 85%
“…This vacuum draws more venous blood back into the heart, resulting in increased cardiac preload, followed by improved cardiac output and vital organ perfusion. Building on recent animal and clinical studies, [1][2][3][4][5] this study compared survival rates after treatment with manual S-CPR versus ACDϩITD CPR in patients with out-ofhospital cardiac arrest.…”
mentioning
confidence: 99%
“…The ITD was designed to create a greater reduction in intrathoracic pressure during inspiration, enhancing the natural vacuum within the chest (26,37). This vacuum promotes an increase in venous return, thereby increasing ventricular preload and subsequent cardiac output (Q) and arterial blood pressure (9,26).…”
mentioning
confidence: 99%
“…Voelckel et al (32) further demonstrated substantial benefit of the combination of the ITD and ACD CPR when compared with standard CPR in a pediatric model of cardiac arrest. Ventricular fibrillation (VF) was induced in 10-kg piglets.…”
Section: Vital Organ Blood Flow In Animalsmentioning
confidence: 99%